2018
DOI: 10.1038/s42003-018-0095-6
|View full text |Cite
|
Sign up to set email alerts
|

Structural and functional studies of the metalloregulator Fur identify a promoter-binding mechanism and its role in Francisella tularensis virulence

Abstract: Francisella tularensis is a Gram-negative bacterium causing tularaemia. Classified as possible bioterrorism agent, it may be transmitted to humans via animal infection or inhalation leading to severe pneumonia. Its virulence is related to iron homeostasis involving siderophore biosynthesis directly controlled at the transcription level by the ferric uptake regulator Fur, as presented here together with the first crystal structure of the tetrameric F. tularensis Fur in the presence of its physiological cofactor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(36 citation statements)
references
References 56 publications
1
35
0
Order By: Relevance
“…It has been generally assumed that when the intracellular "free" iron concentration is elevated, Fur binds "free" ferrous iron and the iron-bound Fur represses the genes encoding for iron uptake systems and stimulates the genes encoding for iron storage proteins (5)(6)(7)(8)(9). The crystallographic studies of the Fur proteins from Escherichia coli (10), Mycobacterium tuberculosis (11), Vibrio cholerae (12), Helicobacter pylori (13), Campylobacter jejuni (14), and Francisella tularensis (15) have revealed that Fur protein exists as a homodimer or tetramer (8) with each monomer containing three putative metal binding sites. The first metal binding site (site 1) is coordinated by His-87, Asp-89, Glu-108, and His-125 (the residue numbers are based on the E. coli Fur), while the second site (site 2) is coordinated by His-33, Glu-81, His-88, and His-90 (12).…”
Section: Introductionmentioning
confidence: 99%
“…It has been generally assumed that when the intracellular "free" iron concentration is elevated, Fur binds "free" ferrous iron and the iron-bound Fur represses the genes encoding for iron uptake systems and stimulates the genes encoding for iron storage proteins (5)(6)(7)(8)(9). The crystallographic studies of the Fur proteins from Escherichia coli (10), Mycobacterium tuberculosis (11), Vibrio cholerae (12), Helicobacter pylori (13), Campylobacter jejuni (14), and Francisella tularensis (15) have revealed that Fur protein exists as a homodimer or tetramer (8) with each monomer containing three putative metal binding sites. The first metal binding site (site 1) is coordinated by His-87, Asp-89, Glu-108, and His-125 (the residue numbers are based on the E. coli Fur), while the second site (site 2) is coordinated by His-33, Glu-81, His-88, and His-90 (12).…”
Section: Introductionmentioning
confidence: 99%
“…These complex modes of action may be modulated by the ability of Fur to compact the DNA structure (80), as well as variations between the structures of the different homologs (75). An additional means of regulation may arise through the quaternary structure of the proteins, given that a subclass of Fur homologs are isolated as tetramers in both the apo-and metalbound states (81,82). The organization of the proteins within the tetramer prevents DNA binding, but dissociation into the active dimers is promoted by the presence of DNA.…”
Section: Fur Familymentioning
confidence: 99%
“…The ferric uptake regulator (Fur) crystal structure was described, and the ability of Fur to bind to promoter sequences containing a Fur box was demonstrated [ 52 ]. Fur is a tetrameric protein that is able to bind specific DNA sequences by its splitting into two dimers [ 52 ].…”
Section: Regulators Necessary For Regulation Of Iron and Metabolismentioning
confidence: 99%
“…Later, it was found that FslE is also required during iron starvation and could act as a membrane receptor for FslA [ 121 ]. The encoding genes belong to fslABCDEF operon (also called fig operon), which is under Fur control [ 52 ] and upregulated during iron starvation [ 52 , 53 ]. Fur is required for full virulence of F. tularensis subsp.…”
Section: Regulators Necessary For Regulation Of Iron and Metabolismentioning
confidence: 99%
See 1 more Smart Citation